2019
DOI: 10.3390/app9214579
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Classification of Advanced Persistent Threats and Attacks Using the Support Vector Machine

Abstract: Traditional network attack and hacking models are constantly evolving to keep pace with the rapid development of network technology. Advanced persistent threat (APT), usually organized by a hacker group, is a complex and targeted attack method. A long period of strategic planning and information search usually precedes an attack on a specific goal. Focus is on a targeted object and customized specific methods are used to launch the attack and obtain confidential information. This study offers an attack detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
0
28
0
3
Order By: Relevance
“…Chu et al have used the combined SVM-RBF method to detect APT attacks with 97.22% accuracy and the FPR value has not been reported in their work [9]. However, we achieved the accuracy of 98.85% using a 6-layer deep learning model, and the FPR value through our proposed model is 1.13.…”
Section: Resultsmentioning
confidence: 60%
“…Chu et al have used the combined SVM-RBF method to detect APT attacks with 97.22% accuracy and the FPR value has not been reported in their work [9]. However, we achieved the accuracy of 98.85% using a 6-layer deep learning model, and the FPR value through our proposed model is 1.13.…”
Section: Resultsmentioning
confidence: 60%
“…It is necessary to mention that they have calculated only the accuracy parameter for the algorithms. In [9], Chu et al have used the NSL-KDD database to detect the attack and have utilized the PCA method to decrease the size of the classified data set and have concluded that the SVM algorithm with the radial basis function as the kernel has better performance comparing to the classification algorithms such as multilayer perceptron (MLP), decision tree of J48 and Naive Bayes reaching a detection accuracy of 97.22%. In an APT attack, since the attacker is following the program with great planning and precision, he makes every effort to behave normally on the network so that the detection tools do not notice his presence, and it makes it difficult to detect the attack.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, cyberattacks are becoming more diverse, sophisticated, targeted, and specialized. Such advanced persistent threats (APTs) [1][2][3] require detailed defense strategies. Research and development projects are being conducted on various information-security solutions to respond to these threats.…”
Section: Introductionmentioning
confidence: 99%